Mediating Effects of Participant and Work Environment Characteristics on the Relationship between Training Design and Implementation with On-The-Job Behaviour - Lau, Yin Yin (2008)
The desirability of management development outdoor programmes leaves many client organizations in the dark about the roles of work environment and participant characteristics mediating between training design and implementation with on-the-job behaviour. The main purpose of the study is to determine mediating effect(s) of work environment and/or participant characteristics between training design and implementation with on-the-job behaviour after attending the management development outdoor programme between 2005 and 2006. The study was a correlational ex post facto design. The study involved 150 participants, drawing randomly from five industries consisting of 191 in population between 2005 and 2006. The response rate was 98.6 percent. The instrument was adopted and adapted from the published research that were the Learning Transfer System Inventory (Holton, Bates and Ruona, 2000), Tracey, Tannenbaum and Kavanagh (1995), Noe and Wilk (1993), McSherry and Taylor (1994), Kontoghiorghes et al (2005), Noe (2002) and Rothwell and Kazanas (1989), Ford (1993), Lewis et al 2004, Lau (2001) and Tai (2006). The instrument used a five points Likert Scale with 1 = strongly disagree and 5 = strongly agree. The reliabilities of all the scales were more than 0.70, which was above the acceptable level (Hair, Black, Babin, Anderson, Tatham, 2006). The content validity of the instrument was reviewed by a panel of judges. The overall measurement model yielded chi-square = 62.69, degree of freedom = 49, non-significance p-value (p > 0.05), ratio = 1.279 (ratio between 1 and 2), CFI = 0.988 (>0.95) and RMSEA = 0.044 (<0.08). It has fulfilled the goodness-of-fit. Data were analyzed using AMOS and SPSS programme. After considering three competing models, the nested model B was the best model based on AIC closer to zero. The results of revised structural model were CMIN/df (ratio) = 1.260 (which is between 1 and 2), RMSEA 0.042 (less than 0.05 indicates good fit), GFI 0.930 (more than 0.90), CFI 0.988 (more than 0.95) and PGFI 0.610. It was found that the relationships between training design and implementation with work environment characteristics, training design and implementation with participant characteristics, and participant characteristics with on-the-job behaviour were positively related to each other. It was not the case for the work environment characteristics that was not significantly related to on-the-job behaviour. The path between work environment characteristics with participant characteristics was omitted due to the best-fit indexes. As such, it is concluded that participant characteristics played as a full mediator between training design and implementation with on-the-job behaviour. Training design and implementation was merely a predictor of the work environment characteristics. The recommendations for the practice are to use the model as a diagnostic tool, for the accountability of the top management, upholding the significance of the human resource department and sustainability of the employability in the market. The recommendations for the future research are such as to look into longitudinal research, quasi experimental design, include baseline measurement data, use multisource feedback and add in qualitative research into the design.